A soy glycinin derived octapeptide protects against MCD diet induced non-alcoholic fatty liver disease in mice - Peng Ma; Rongrong Huang; Yu Ou (Food Science and Human Wellness)
Soy glycinin derived octapeptide (SGP8) is a peptide obtained from degradation of the soy glycinin, whose amino acid sequence is IAVPGEVA. To determine the effect of SGP8 on non-alcoholic fatty liver disease (NAFLD), steatosis HepG2 cells were induced by 1 mmol/L free fatty acid (FFA) and C57BL/6J mice were fed with methionine-choline deficient (MCD) diet for 3 weeks to establish NAFLD model. The results of oil red O staining and total cholesterol (TC)/triglyceride (TG) contents showed that SGP8 could significantly reduce the lipid content of steatosis HepG2 cells. In vivo, SGP8 lowered plasma alanine aminotransferase (ALT) and low density lipoprotein (LDL) content, normalized hepatic superoxide dismutase (SOD) and malondialdehyde (MDA) production, and reduced the severity of liver inflammation. The results of Western blotting showed that SGP8 increased expression of Sirtuin-1 (SIRT1) and phosphorylation level of AMP activated protein kinase (AMPK) in hepatocytes. Through activation of SIRT1/AMPK pathway, SGP8 downregulated the expression of sterol regulatory element binding protein 1c (SREBP-1c) and its target genes ACC and FAS expression levels, and increased the phosphorylation level of acetyl CoA carboxylase (ACC). Furthermore, SGP8 also upregulated the expression of transcription factor peroxisome proliferator activated receptor α (PPARα), which was regulated by SIRT1/AMPK pathway, and its target gene CPT1 level. In conclusion, SGP8 might improve NAFLD by activating the SIRT1/AMPK pathway. Our data suggest that SGP8 may act as a novel and potent therapeutic agent against NAFLD.